FREQUENCY OF OCULAR COMPLICATIONS OF LEPROSY IN INSTITUTIONALIZED PATIENTS IN NWFP PAKISTAN - Khan, Tajamul; Awan, Abdul Aziz; Kazmi, Hasan Sajid; Shah, Ashfaq Ali; Muhammad, Sardar; Muhammad, Shad (Journal of Ayub Medical College Abbottabad, 2002)
Background: There is no systemic disease, which so frequently gives rise to disorders of the eye as leprosy does. The study was conducted to determine the prevalence and gravity of ocular complications in institutionalized leprosy patients in NWFP. It is important to provide necessary information to leprosy health workers and general physicians in order to sensitize them to early detection and treatment or referral to appropriate centre. Methods: A prospective study of ocular complications of leprosy patients was conducted at the leprosy centre of Lady Reading Hospital Peshawar and the Leprosy Hospital Balakot, district Mansehra. The study included a record of the name, age, sex, type, duration of disease and completion of multi-drug therapy (MDT). Classification of the patients was done according to Ridley and Jopling 5-group system. Visual acuity was tested by Snellen chart and those patients having a vision of less than 3/60 were labelled as blind. Ocular adnexa were examined by naked eye and lacrimal sac regurgitation test was done. Slit lamp biomicroscopy was done for anterior segment examination and direct ophthalmoscope was used for fundoscopy. Results: The authors studied 143 patients in the above mentioned leprosy centres. Out of these, 59 had lepromatous leprosy, 39 borderline tuberculoid leprosy, 9 tuberculoid leprosy, 33 borderline lepromatous leprosy, and 33 borderline leprosy. The majority of patients came from the northern districts of NWFP, including Malakand division and district Mansehra. The male to female ratio was 4:1. The age of the patients ranged from 14 to 80 years and the duration of the disease ranged from 1 year to 48 years. Ocular complications were found in 73 % of the patients. These complications included loss of eyebrows in 57 patients, loss of eyelashes in 37, corneal changes (including opacity, ulceration, and/or anaesthesia) in 44, iridocyclitis in 31, lagophthalmos in 36, ectropion in 13, and chronic dacryocystitis in 3. Of the total of 15 (11%) patients who went blind from ocular complications, 16 eyes did so due to corneal opacities, 6 eyes due to cataract, 5 eyes due to chronic anterior uveitis and one eye due to corneal ulcer, panophthalmitis and phthisis bulbi each. Conclusions: A significant number of leprosy patients (73%) have ocular complications. The frequency of ocular complications increases with the increasing age and duration of disease of the patients.